MODERNISASI PROSES PEMBELAJARAN SEBAGAI UPAYA MENINGKATKAN PERHATIAN BELAJAR SISWA DI MADRASAH ALIYAH SWASTA AL WASHLIYAH MEDAN - Alkausar Saragih; Ismed Batubara; Bonanda Japatani Siregar (Jurnal Bilqolam Pendidikan Islam, 2023)
The current era of information technology development has unwittingly changed the global world order which inevitably becomes a challenge for the world of education today. Education modification should also welcome the development of information technology to be developed in the learning process to be more effective and attract the attention of students so that it is hoped that the knowledge to be conveyed can be easily understood. The development of information technology is marked by the emergence of sophisticated tools that can be utilized in the learning process in schools. This study aims to see the modification in classroom learning carried out by teachers in every learning process, especially at MAS Lab IKIP Al Washliyah Medan, the research method is a qualitative descriptive method with data collection through interviews, observations, and other instruments that are categorized to support this research. The results of this study found that the implementation of learning in schools, especially at MAS Lab IKIP Al Washliyah Medan, has embraced learning moderenization, this can be seen from learning facilities that have used technological devices in accordance with the times, such as learning using laptob facilities, computers, infocus, and other learning facilities.